Optical laminate with surface protective film and method for manufacturing display system
By using two layers of surface protective films on the optical laminate of VR goggles and adjusting the thickness and peeling force of its adhesive layer, the bubble misdetection and protective film peeling problems during defect inspection during assembly process are solved, and optical Multiple inspections and stable protection of the stacked body.
Patent Information
- Application Number
- CN202380027326.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-03-07
- Publication Date
- 2025-01-10
AI Technical Summary
The optical laminated body of VR goggles requires multiple defect inspections during assembly, and in the prior art, the surface protective film is prone to bubbles or poor peeling during peeling, resulting in the problem of false detection and peeling of the protective film together.
By adding two layers of surface protective films to the optical laminate and adjusting the adhesive layer thickness and peel force relationship of the outer and inner protective films, it is ensured that bubble generation and stable peeling of the protective film are avoided during multiple defect inspections.
It effectively suppresses the generation of bubbles between the surface protective films, prevents misdetection, and ensures that the optical laminate performs multiple defect inspections under the protection state, improving the reliability and efficiency of the assembly process.
Smart Images

Figure CN119301508A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate with a surface protection film and a method for producing a display system using the optical laminate with a surface protection film. Background Art
[0002] Image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices) are rapidly becoming popular. In image display devices, optical components such as polarization components and phase difference components are generally used to realize image display and improve image display performance (e.g., refer to Patent Document 1).
[0003] In recent years, new uses of image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have begun to be commercialized. In VR goggles, since the image displayed on the display panel is magnified for visual recognition by the viewer, stricter defect management is required for optical laminates used in VR goggles than for optical laminates used in existing image display devices.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-103286 Summary of the invention
[0007] Problems to be solved by the invention
[0008] As described above, strict defect management is required for the optical laminate used in VR goggles, so multiple defect inspections may be performed until it becomes the final product, more specifically, until it is provided for the final assembly process. On the other hand, it is preferred that the surface of the optical laminate is protected until it is provided for the final assembly process. To this end, the main purpose of the present invention is to provide an optical laminate that can be applied to VR goggles and can be inspected for defects multiple times while the surface is protected.
[0009] Solutions to the problem
[0010] The inventors of the present invention have conducted research to solve the above-mentioned problems, and as a result, obtained the following concept: by subjecting an optical laminate in a state protected by a surface protective film to defect inspection; and by further protecting the inspection object (i.e., the optical laminate in a state protected by a surface protective film) with another surface protective film, the above-mentioned problems can be solved. Based on this concept, it is known that when an optical laminate with a surface protective film having two surface protective films laminated thereon is produced and subjected to defect inspection, bubbles will be generated between the two surface protective films, and the bubbles may sometimes be mistakenly detected as defects of the optical laminate. It is also known that when the outer surface protective film is to be peeled off to obtain an optical laminate in a state protected only by the inner surface protective film, the inner surface protective film may sometimes be peeled off together.
[0011] In view of the above problems, the inventors of the present invention have found that by increasing the thickness of the adhesive layer of the outer surface protective film and adjusting the relationship between the peeling force of the outer surface protective film and the peeling force of the inner surface protective film, these problems can be avoided and the above-mentioned problems can be solved at the same time, thereby completing the present invention.
[0012] According to one aspect of the present invention, there are provided the optical layered body with a surface protection film of [1] to [8], and the method for manufacturing a display system of [9].
[0013] [1] An optical laminate with a surface protection film, comprising: an optical laminate comprising at least one optical component used for goggles with a display; and a first surface protection film and a second surface protection film sequentially bonded to one surface of the optical laminate toward the outside, wherein the first surface protection film has a first substrate and a first adhesive layer laminated on the first substrate, and the second surface protection film has a second substrate and a second adhesive layer laminated on the second substrate, the thickness of the second adhesive layer is greater than 8 μm, and the peeling force P1 of the first surface protection film relative to the optical laminate and the peeling force P2 of the second surface protection film relative to the first surface protection film satisfy the relationship P2 / P1≤0.8.
[0014] [2] The optical laminate with a surface protection film according to [1], wherein the peeling force P2 of the second surface protection film with respect to the first surface protection film is 0.5 N / 50 mm or less.
[0015] [3] The optical layered body with a surface protection film according to [1] or [2], wherein the total light transmittance of the first surface protection film and the second surface protection film is 85% or more respectively.
[0016] [4] An optical laminate with surface protection films according to any one of [1] to [3], wherein the ratio (L2 / L1) of the total light transmittance L1 of the first surface protection film to the total light transmittance L2 of the second surface protection film is 0.8 to 1.2.
[0017] [5] An optical laminate with a surface protection film according to any one of [1] to [4], wherein the optical laminate: (1) has an absorption-type polarization component, a first phase difference component and a protection component in sequence toward the first surface protection film; or, (2) has a second phase difference component and a protection component in sequence toward the first surface protection film; or (3) has a reflection-type polarization component and a protection component in sequence toward the first surface protection film.
[0018] [6] The optical laminate with a surface protection film according to [5], wherein the protection member includes a surface treatment layer, and the first surface protection film is bonded to the surface treatment layer.
[0019] [7] The optical laminate with a surface protection film according to [6], wherein the surface treatment layer includes an antireflection layer, and the first surface protection film is bonded to the antireflection layer.
[0020] [8] The optical layered body with a surface protection film according to any one of [1] to [7], wherein the optical layered body has a pressure-sensitive adhesive layer on a surface opposite to a side to which the first surface protection film and the second surface protection film are bonded.
[0021] [9] A method for manufacturing a display system, the method comprising, in sequence: inspecting an optical laminate with a surface protection film as described in any one of [1] to [8] for defects; bonding another component to the side of the optical laminate with a surface protection film opposite to the side to which the first surface protection film and the second surface protection film are bonded to obtain a secondary laminate with a surface protection film; peeling the second surface protection film from the secondary laminate with the surface protection film; inspecting the secondary laminate with the surface protection film for defects; and peeling the first surface protection film from the secondary laminate with the surface protection film to obtain a secondary laminate, wherein the display system is a pair of goggles with a display.
[0022] Effects of the Invention
[0023] According to the optical layered body with surface protection film of the embodiment of the present invention, the generation of bubbles between the surface protection films (resulting in erroneous detection of defects) and the problem of poor peeling can be suppressed, and the optical layered body can be inspected for defects multiple times while its surface is protected. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic cross-sectional view of an optical layered body with a surface protection film according to one embodiment of the present invention.
[0025] Figure 2 This is a schematic diagram showing a schematic configuration of a display system to which the optical layered body according to the embodiment of the present invention can be applied.
[0026] Figure 3 It is shown that it can be used for Figure 2 A schematic cross-sectional view of an example of an optical stack of the display system shown.
[0027] Figure 4 It is shown that it can be used for Figure 2 A schematic cross-sectional view of an example of an optical stack of the display system shown.
[0028] Figure 5 It is shown that it can be used for Figure 2 A schematic cross-sectional view of an example of an optical stack of the display system shown.
[0029] Fig. 6A This is a schematic diagram for explaining a method for manufacturing a display system according to an embodiment of the present invention.
[0030] Figure 6B Then Fig. 6A .
[0031] Figure 6C Then Figure 6B .
[0032] Fig.6D Then Figure 6C .
[0033] Fig. 6E Then Fig.6D .
[0034] Explanation of symbols
[0035] 2 Display system
[0036] 4 Lens section
[0037] 10 Polarization component
[0038] 12 Display components
[0039] 14 Reflective polarizing element
[0040] 16. First lens unit
[0041] 18 Half Mirror
[0042] 20 first phase difference member
[0043] 22. Second phase difference member
[0044] 24 Second lens unit
[0045] 100 Optical laminate
[0046] 110 First surface protective film
[0047] 120 Second surface protective film
[0048] 200 Optical laminate with surface protection film DETAILED DESCRIPTION
[0049] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. In addition, in order to explain more clearly, the accompanying drawings sometimes schematically show the width, thickness, shape, etc. of each part compared with the embodiments, but this is only an example and does not limit the interpretation of the present invention.
[0050] (Definition of Terms and Symbols)
[0051] The definitions of terms and symbols in this specification are as follows.
[0052] (1) Refractive index (nx, ny, nz)
[0053] "nx" is the refractive index in the direction where the refractive index in the plane reaches the maximum (ie, the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and "nz" is the refractive index in the thickness direction.
[0054] (2) In-plane phase difference (Re)
[0055] "Re(λ)" is the in-plane phase difference measured at 23°C with light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C with light of wavelength 550nm. When the thickness of the layer (film) is d(nm), Re(λ) can be calculated by the formula: Re(λ) = (nx-ny)×d.
[0056] (3) Retardation in the thickness direction (Rth)
[0057] "Rth(λ)" is the phase difference in the thickness direction measured at 23°C with light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction measured at 23°C with light of wavelength 550nm. When the thickness of the layer (film) is d(nm), Rth(λ) can be calculated by the formula: Rth(λ) = (nx-nz)×d.
[0058] (4) Nz coefficient
[0059] The Nz coefficient can be calculated by Nz=Rth / Re.
[0060] (5) Angle
[0061] In this specification, when an angle is mentioned, the angle includes both clockwise and counterclockwise relative to the reference direction. Therefore, for example, "45°" means 45° clockwise or counterclockwise. In addition, in this specification, "substantially parallel" includes the case within the range of 0°±10°, for example, 0°±5°, preferably 0°±3°, and more preferably 0°±1°, and "substantially orthogonal" includes the case within the range of 90°±10°, for example, 90°±5°, preferably 90°±3°, and more preferably 90°±1°.
[0062] A. Optical laminate with surface protection film
[0063] Figure 1 It is a schematic cross-sectional view of an optical laminate with a surface protective film according to an embodiment of the present invention. The optical laminate 200 with a surface protective film comprises: an optical laminate 100 including at least one optical component used for goggles with a display; and a first surface protective film 110 and a second surface protective film 120 sequentially bonded to the surface of one side of the optical laminate 100 toward the outside. The first surface protective film 110 comprises a first substrate 112 and a first adhesive layer 114 laminated on the first substrate 112. The second surface protective film 120 comprises a second substrate 122 and a second adhesive layer 124 laminated on the second substrate 122. The first surface protective film 110 and the second surface protective film 120 are process components temporarily bonded (temporarily bonded) to the optical laminate 100, and are peeled off and removed when the optical laminate 100 is provided for use. It should be noted that in this specification, the first surface protective film is sometimes referred to as the inner surface protective film, and the second surface protective film is sometimes referred to as the outer surface protective film.
[0064] The optical laminate with surface protection films can be manufactured by laminating the first surface protection film and the second surface protection film on the surface of one side of the optical laminate. The first surface protection film and the second surface protection film can be sequentially laminated on the surface of one side of the optical laminate, or the laminate of the first surface protection film and the second surface protection film can be laminated to the optical laminate. During the period until the first surface protection film and the second surface protection film are used, the adhesive layer side surface can be protected by a release liner.
[0065] A-1. First surface protective film (inner surface protective film)
[0066] like Figure 1 As shown, the first surface protection film 110 includes a first substrate 112 and a first adhesive layer 114 laminated on the first substrate 112 .
[0067] The total light transmittance L1 of the first surface protective film is, for example, 85% or more, preferably 88% or more, and more preferably 90% or more. When the total light transmittance L1 is within the above range, even when the surface of the optical laminate is protected by the first surface protective film, precise defect inspection can be appropriately performed.
[0068] The haze of the first surface protective film is, for example, 5% or less, preferably 4% or less, more preferably 3% or less, and typically 0.05% or more. When the haze is within the above range, even when the surface of the optical laminate is protected by the first surface protective film, precise defect inspection can be appropriately performed. The surface protective film having the haze within the above range can be obtained, for example, by using a substrate and / or adhesive layer with a low haze.
[0069] The peeling force P1 (peeling speed: 300 mm / min, peeling angle: 180°) of the first surface protective film relative to the optical laminate is, for example, 1.0 N / 50 mm or less, preferably 0.5 N / 50 mm or less, more preferably 0.3 N / 50 mm or less, for example, 0.05 N / 50 mm or more, preferably 0.08 N / 50 mm or more, more preferably 0.10 N / 50 mm or more. When the peeling force P1 is within the above range, it is possible to appropriately prevent the first surface protective film from being peeled off together with the second surface protective film when the second surface protective film is peeled off.
[0070] <First base material>
[0071] The first substrate is formed by any appropriate resin film that can be used as a surface protection film. As a specific example of the material that becomes the main component of the resin film, it can be enumerated: cycloolefins (COP) such as polynorbornenes, polyesters such as polyethylene terephthalate (PET), celluloses such as triacetyl cellulose (TAC), polycarbonates (PC), (methyl) acrylic acid, polyvinyl alcohol, polyamide, polyimide, polyether sulfone, polysulfone, polystyrene, polyolefin, acetate and other transparent resins. In addition, it can also be enumerated: (methyl) acrylic acid, carbamate, (methyl) acrylic acid carbamate, epoxy, silicone and other thermosetting resins or ultraviolet curing resins. It should be noted that "(methyl) acrylic resin" refers to acrylic resin and / or methacrylic resin. In addition, for example, glassy polymers such as siloxane polymers can also be enumerated. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imido group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl and nitrile group in the side chain can be used, for example, a resin composition having an alternating copolymer formed by isobutylene and N-methylmaleimide and acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above-mentioned resin composition. The material of the resin film can be used alone or in combination.
[0072] The first substrate preferably includes at least one transparent resin selected from COP, PET, TAC, PC and (meth) acrylic acid, more preferably includes at least one transparent resin selected from COP, PET, PC and (meth) acrylic acid, and further preferably includes at least one transparent resin selected from COP, PET and PC. If the first substrate includes the above-mentioned transparent resin, it is possible to more stably reduce false detection caused by the surface protection film in defect inspection.
[0073] The first substrate may also contain antioxidants, ultraviolet absorbers, light stabilizers, nucleating agents, fillers, pigments, surfactants, antistatic agents, etc. An easy-adhesion layer, an easy-slip layer, an anti-blocking layer, an antistatic layer, an anti-reflection layer, an anti-oligomer layer, etc. may also be provided on the surface of the first substrate (the surface opposite to the first adhesive layer).
[0074] The thickness of the first substrate is typically 5 μm or more, preferably 20 μm or more, and is typically 200 μm or less, preferably 100 μm or less.
[0075] <First adhesive layer>
[0076] The first adhesive layer is composed of any appropriate adhesive. The adhesive constituting the first adhesive layer typically contains at least one adhesive selected from (meth)acrylic adhesives, urethane adhesives, and silicone adhesives. Preferably, the first adhesive layer contains a (meth)acrylic adhesive.
[0077] The (meth)acrylic adhesive contains a polymer having a (meth)acrylic acid alkyl ester as a monomer component as a main component (hereinafter referred to as a (meth)acrylic acid polymer). In other words, the (meth)acrylic acid polymer contains a structural unit derived from the (meth)acrylic acid alkyl ester. The content ratio of the structural unit derived from the (meth)acrylic acid alkyl ester in the (meth)acrylic acid polymer is typically 50% by mass or more, preferably 80% by mass or more, more preferably 93% by mass or more, for example, 100% by mass or less, preferably 98% by mass or less.
[0078] The alkyl group of the (meth)acrylic acid alkyl ester may be linear or branched. The number of carbon atoms of the alkyl group is, for example, 1 to 18. Examples of the alkyl group include methyl, ethyl, butyl, 2-ethylhexyl, decyl, isodecyl, and octadecyl. The (meth)acrylic acid alkyl ester may be used alone or in combination. The average number of carbon atoms of the alkyl group is preferably 3 to 10.
[0079] In addition to the structural unit derived from the alkyl (meth)acrylate, the (meth)acrylic polymer may also contain a structural unit derived from a comonomer that can polymerize with the alkyl (meth)acrylate. Examples of the comonomer include carboxyl group-containing monomers and hydroxyl group-containing monomers. The comonomers may be used alone or in combination.
[0080] The carboxyl group-containing monomer is a compound containing a carboxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth) acryloyl and vinyl. As the carboxyl group-containing monomer, for example, (meth) acrylic acid, (meth) carboxyethyl acrylate, maleic acid, fumaric acid, crotonic acid, preferably (meth) acrylic acid. If the (meth) acrylic polymer contains a structural unit derived from the carboxyl group-containing monomer, it is possible to achieve an improvement in the adhesive properties of the adhesive layer. In the case where the (meth) acrylic polymer contains a structural unit derived from the carboxyl group-containing monomer, the content ratio of the structural unit derived from the carboxyl group-containing monomer is preferably 0.01% by mass or more and 10% by mass or less.
[0081] Hydroxyl-containing monomers are compounds containing hydroxyl groups in their structures and containing polymerizable unsaturated double bonds such as (meth) acryloyl groups and vinyl groups. As hydroxyl-containing monomers, for example, 2-hydroxyethyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, methyl acrylate (4-hydroxymethylcyclohexyl), 2-hydroxyethyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, and 2-hydroxyethyl (meth) acrylate can be preferably cited. If the (meth) acrylic polymer includes a structural unit derived from a hydroxyl-containing monomer, the durability of the adhesive layer can be improved. In the case where the (meth) acrylic polymer includes a structural unit derived from a hydroxyl-containing monomer, the content ratio of the structural unit derived from the hydroxyl-containing monomer is preferably 0.01% by mass or more and 10% by mass or less in the (meth) acrylic polymer.
[0082] The weight average molecular weight Mw of the (meth)acrylic polymer is, for example, 100,000 to 2,000,000, or preferably 200,000 to 1,000,000.
[0083] In addition, the (meth) acrylic adhesive may contain a crosslinking agent. As the crosslinking agent, representative examples include organic crosslinking agents and multifunctional metal chelates, and preferably organic crosslinking agents may be mentioned. As the organic crosslinking agent, for example, isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, and imine crosslinking agents may be mentioned, and more preferably isocyanate crosslinking agents may be mentioned. When the adhesive contains a crosslinking agent, the content ratio of the crosslinking agent is usually 0.01 mass parts or more and 15 mass parts or less relative to 100 mass parts of the (meth) acrylic polymer.
[0084] The above adhesives ((meth)acrylic adhesives, urethane adhesives and silicone adhesives) may also contain various additives in appropriate proportions as required. By adjusting the composition of the base polymer (e.g., the type and content ratio of the monomer, the type and content ratio of the crosslinking agent, etc.), the molecular weight of the base polymer, the type or content ratio of the additives, etc., an adhesive layer having the desired adhesiveness to the adherend can be obtained.
[0085] Examples of the additives include polymerization initiators, solvents, polymerization catalysts, crosslinking catalysts, silane coupling agents, tackifiers, plasticizers, softeners, anti-degradation agents, fillers, colorants (pigments, dyes, etc.), light stabilizers, ultraviolet absorbers, antioxidants, surfactants, antistatic agents, chain transfer agents, and the like.
[0086] The thickness of the first pressure-sensitive adhesive layer is, for example, 10 μm or more, preferably 12 μm or more, for example, 40 μm or less, preferably 30 μm or less, more preferably 25 μm or less. When the first pressure-sensitive adhesive layer has such a thickness, the optical laminate can be well protected.
[0087] In one embodiment, the ratio (T1 / T2) of the thickness T1 of the first adhesive layer to the thickness T2 of the second adhesive layer of the second surface protective film is, for example, 2 or less, preferably 1.8 or less, more preferably 1.5 or less, further preferably 1.2 or less, further preferably 1 or less, particularly preferably 0.8 or less, for example 0.1 or more, preferably 0.2 or more, more preferably 0.3 or more, further preferably 0.4 or more, further more preferably 0.5 or more. When the ratio (T1 / T2) is within the above range, the generation of bubbles between the first surface protective film and the second surface protective film and the suppression of poor peeling can be appropriately performed. In addition, the optical laminate can be well protected.
[0088] The first adhesive layer can be formed on the surface of the first substrate by direct writing or by transfer. In the case of direct writing, the adhesive is directly applied to the surface of the first substrate to form the first adhesive layer. In the case of transfer, after the adhesive is applied to the surface of the release liner to form the first adhesive layer, the substrate is attached to the first adhesive layer. In particular, when the first substrate contains an amorphous resin with a relatively low glass transition temperature Tg (for example, below 150°C), the first adhesive layer is preferably formed by a transfer process. If it is a transfer process, it is possible to suppress the influence of the high temperature during drying necessary for the formation of the first adhesive layer on the first substrate.
[0089] A-2. Second surface protective film (outer surface protective film)
[0090] like Figure 1 As shown, the second surface protection film 120 includes a second base material 122 and a second adhesive layer 124 laminated on the second base material.
[0091] The total light transmittance L2 of the second surface protective film is, for example, 85% or more, preferably 88% or more, and more preferably 90% or more. When the total light transmittance L2 is within the above range, even when the surface of the optical laminate is protected by the first surface protective film and the second surface protective film, precise defect inspection can be appropriately performed.
[0092] The ratio (L2 / L1) of the total light transmittance L1 of the first surface protective film to the total light transmittance L2 of the second surface protective film is, for example, 0.8 to 1.2, preferably 0.85 to 1.15, and more preferably 0.9 to 1.1. When the ratio (L2 / L1) is within the above range, even when the surface of the optical laminate is protected by the first surface protective film and the second surface protective film, precise defect inspection can be appropriately performed.
[0093] The haze of the second surface protective film is, for example, 5% or less, preferably 4% or less, more preferably 3% or less, and representatively, 0.05% or more. When the haze is within the above range, even when the surface of the optical laminate is protected by the first surface protective film and the second surface protective film, precise defect inspection can be appropriately performed.
[0094] The peeling force P2 (peeling speed: 300 mm / min, peeling angle: 180°) of the second surface protective film relative to the first surface protective film is, for example, 0.5 N / 50 mm or less, preferably 0.3 N / 50 mm or less, more preferably 0.2 N / 50 mm or less, and further preferably 0.1 N / 50 mm or less, for example, 0.01 N / 50 mm or more, preferably 0.03 N / 50 mm or more, and further preferably 0.05 N / 50 mm or more. When the peeling force P2 is within the above range, when the second surface protective film is peeled off, the problem of poor peeling of the first surface protective film together with the second surface protective film can be suitably prevented. In addition, the generation of bubbles between the first surface protective film and the second surface protective film can be suitably suppressed.
[0095] The ratio (P2 / P1) of the peeling force P2 (peeling speed: 300 mm / min, peeling angle: 180°) of the second surface protective film relative to the first surface protective film and the peeling force P1 (peeling speed: 300 mm / min, peeling angle: 180°) of the first surface protective film relative to the optical laminate is typically 0.8 or less, preferably 0.6 or less, more preferably 0.5 or less, for example 0.2 or more. When the peeling force ratio (P2 / P1) is within the above range, it is possible to appropriately prevent the first surface protective film from being peeled off together with the second surface protective film when the second surface protective film is peeled off. In addition, the generation of bubbles between the first surface protective film and the second surface protective film can be appropriately suppressed.
[0096] <Second base material>
[0097] The second substrate may be formed of any appropriate resin film that can be used as a surface protection film. Specific examples of the material that is the main component of the resin film are as described above for the first substrate.
[0098] The second substrate may also contain antioxidants, ultraviolet absorbers, light stabilizers, nucleating agents, fillers, pigments, surfactants, antistatic agents, etc. An easy-adhesion layer, an easy-slip layer, an anti-blocking layer, an antistatic layer, an anti-reflection layer, an anti-oligomer layer, etc. may also be provided on the surface of the second substrate (the surface opposite to the second adhesive layer).
[0099] The thickness of the second substrate is typically 5 μm or more, preferably 20 μm or more, and is typically 200 μm or less, preferably 100 μm or less.
[0100] <Second adhesive layer>
[0101] The second adhesive layer is composed of any appropriate adhesive. Typically, the adhesive constituting the second adhesive layer contains at least one adhesive selected from (meth) acrylic adhesives, urethane adhesives, and silicone adhesives. Preferably, the second adhesive layer contains a (meth) acrylic adhesive. The details of the (meth) acrylic adhesive are as described above for the first adhesive layer.
[0102] The above-mentioned adhesive ((meth) acrylic adhesive, urethane adhesive and silicone adhesive) may contain a base polymer (or its constituent monomer components) and additives used as needed. Specific examples of the additives are described above for the first adhesive layer. By adjusting the composition of the base polymer (for example, the type and content ratio of the monomer, the type and content ratio of the cross-linking agent, etc.), the molecular weight of the base polymer, the type or content ratio of the additive, etc., an adhesive layer having the desired adhesion to the adherend can be obtained.
[0103] The thickness of the second adhesive layer is typically 8 μm or more, preferably 10 μm or more, more preferably 15 μm or more, for example, 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. When the second adhesive layer has the above thickness, the generation of bubbles between the first surface protective film and the second surface protective film can be suppressed, and the defect inspection of the optical laminate can be performed well in the state where these surface protective films are attached.
[0104] As a method for forming the second pressure-sensitive adhesive layer, the same method as the method for forming the first pressure-sensitive adhesive layer may be mentioned.
[0105] A-3. Optical laminate
[0106] The optical laminate includes at least one optical component and is used for goggles with a display. Examples of the optical component include an absorption-type polarization component, a reflection-type polarization component, a phase difference component, etc. The optical laminate may have an adhesive layer on the side opposite to the side on which the first surface protection film and the second surface protection film are attached.
[0107] A-3-1. Display system to which optical laminate can be applied
[0108] Figure 2 Schematic diagram showing the simplified structure of a display system (goggles with display) to which an optical laminate can be applied. Figure 2 , the configuration and shape of each component of the display system 2 are schematically shown. The display system 2 includes a display element 12, a reflective polarization component 14, a first lens unit 16, a half mirror 18, a first phase difference component 20, a second phase difference component 22, and a second lens unit 24. The reflective polarization component 14 is arranged on the display surface 12a side of the display element 12, that is, in front, and can reflect the light emitted from the display element 12. The first lens unit 16 is arranged on the optical path between the display element 12 and the reflective polarization component 14, and the half mirror 18 is arranged between the display element 12 and the first lens unit 16. The first phase difference component 20 is arranged on the optical path between the display element 12 and the half mirror 18, and the second phase difference component 22 is arranged on the optical path between the half mirror 18 and the reflective polarization component 14. Although not shown in the figure, the display system 2 may further include an absorptive polarization component between the reflective polarization component 14 and the second lens unit 24.
[0109] Components arranged in front of the half mirror (in the illustrated example, the half mirror 18 , the first lens unit 16 , the second phase difference element 22 , the reflective polarization element 14 , and the second lens unit 24 ) are sometimes collectively referred to as a lens unit (lens unit 4 ).
[0110] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. Light emitted from the display surface 12a passes through, for example, a polarizing member 10 that may be included in the display element 12 and then emitted as first linearly polarized light.
[0111] The first phase difference member 20 includes a first λ / 4 member capable of converting the first linear polarization light incident on the first phase difference member 20 into a first circular polarization light. When the first phase difference member does not include a member other than the first λ / 4 member, the first phase difference member may be equivalent to the first λ / 4 member. The first phase difference member 20 may be integrally provided on the display element 12.
[0112] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflective polarization member 14 toward the reflective polarization member 14. The half mirror 18 is integrally provided with the first lens portion 16.
[0113] The second phase difference member 22 includes a second λ / 4 member that allows the light reflected by the reflective polarization member 14 and the half mirror 18 to pass through the reflective polarization member 14. When the second phase difference member does not include a member other than the second λ / 4 member, the second phase difference member may be equivalent to the second λ / 4 member. The second phase difference member 22 may be integrally provided on the first lens portion 16.
[0114] The first circularly polarized light emitted from the first λ / 4 member included in the first phase difference member 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member included in the second phase difference member 22. The second linearly polarized light emitted from the second λ / 4 member does not pass through the reflective polarization member 14, but is reflected toward the half mirror 18. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarization member 14 is the same direction as the reflection axis of the reflective polarization member 14. Therefore, the second linearly polarized light incident on the reflective polarization member 14 is reflected by the reflective polarization member 14.
[0115] The second linear polarized light reflected by the reflective polarization member 14 is converted into the second circular polarized light by the second λ / 4 member included in the second phase difference member 22, and the second circular polarized light emitted from the second λ / 4 member passes through the first lens unit 16 and is reflected by the half mirror 18. The second circular polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linear polarized light by the second λ / 4 member included in the second phase difference member 22. The third linear polarized light is transmitted through the reflective polarization member 14. At this time, the polarization direction of the third linear polarized light incident on the reflective polarization member 14 is the same direction as the transmission axis of the reflective polarization member 14. Therefore, the third linear polarized light incident on the reflective polarization member 14 is transmitted through the reflective polarization member 14.
[0116] As described above, the display system 2 may include an absorptive polarizing element (representatively, an absorptive polarizing film) in front of the reflective polarizing element 14 (on the side close to the eyes). The reflection axis of the reflective polarizing element 14 and the absorption axis of the absorptive polarizing element may be arranged substantially parallel to each other. Thus, the third linear polarized light after passing through the reflective polarizing element 14 may directly pass through the absorptive polarizing element. The reflective polarizing element and the absorptive polarizing element may be laminated together, for example, via an adhesive layer.
[0117] The light transmitted through the reflective polarization element 14 passes through the second lens portion 24 and enters the eye 26 of the user.
[0118] For example, the absorption axis of the polarization component 10 included in the display element 12 and the reflection axis of the reflective polarization component 14 can be arranged approximately parallel to each other, or can be arranged approximately orthogonal to each other. The angle formed by the absorption axis of the polarization component 10 included in the display element 12 and the slow axis of the 1st λ / 4 component included in the first phase difference component 20 is, for example, 40° to 50°, 42° to 48°, or approximately 45°. The angle formed by the absorption axis of the polarization component included in the display element 12 and the slow axis of the 2nd λ / 4 component included in the second phase difference component 22 is, for example, 40° to 50°, 42° to 48°, or approximately 45°.
[0119] In the lens portion 4, a space can be formed between the first lens portion 16 and the second lens portion 24. In this case, the component arranged between the first lens portion 16 and the second lens portion 24 is preferably provided integrally in any one of the first lens portion 16 and the second lens portion 24. For example, the component arranged between the first lens portion 16 and the second lens portion 24 is preferably integrated with any one of the first lens portion 16 and the second lens portion 24 via an adhesive layer. According to such a method, for example, the operability of each component can be excellent. The adhesive layer can be formed by an adhesive or an adhesive. Specifically, the adhesive layer can be an adhesive layer or an adhesive layer. The thickness of the adhesive layer is, for example, 0.05μm to 30μm.
[0120] A-3-2. Configuration of optical laminate
[0121] Figure 3 is able to Figure 2 A simplified cross-sectional view of an optical laminate used in an exemplary display system. The optical laminate 100a includes an adhesive layer 31, a polarizing element 10, a first phase difference element 20, and a first protective element 41 in sequence. The polarizing element 10, the first phase difference element 20, and the first protective element 41 are stacked together via adhesive layers 51 and 52. The adhesive layers 51 and 52 are typically adhesive layers or adhesive layers, preferably adhesive layers. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm. During the period until it is provided for use, the surface of the adhesive layer 31 is protected by a release liner 61. It should be noted that the first surface protective film and the second surface protective film are adhered to the side surface of the first protective element 41 of the optical laminate 100a.
[0122] exist Figure 3In the example shown, the first phase difference component 20 includes, in addition to the first λ / 4 component 20a, a component (so-called positive C plate) 20b whose refractive index characteristics can show the relationship of nz>nx=ny. The first phase difference component 20 has a stacked structure of the first λ / 4 component 20a and the first positive C plate 20b. Unlike the example shown in the figure, the first positive C plate 20b may be located closer to the polarization component 10 side than the first λ / 4 component 20a, and the first positive C plate 20b may also be omitted. The first λ / 4 component 20a and the first positive C plate 20b may be stacked, for example, via an adhesive layer not shown. In addition, in the first phase difference component 20, the angle between the absorption axis of the polarization component 10 and the slow axis of the first λ / 4 component 20a is preferably 40° to 50°, more preferably 42° to 48°, for example, about 45°.
[0123] The optical laminate 100a can be applied to, for example, Figure 2 The manufacture of a display system of an embodiment in which the first phase difference member 20 is integrally arranged on the display element 12 in the exemplary display system. For example, by peeling off the release liner 61 from the optical laminate 100a, and attaching the polarization member 10 to the liquid crystal unit in a manner that makes the polarization member 10 become the front side (visible side) polarization member of the liquid crystal unit together with the back side polarization member, a display system in which the first phase difference member 20 and the liquid crystal panel (display element) are set as one can be manufactured. In addition, for example, by peeling off the release liner 61 from the optical laminate 100a, and attaching it to the front of the organic EL panel via the adhesive layer 31, a display system in which the first phase difference member 20 and the organic EL panel (display element) are set as one can be manufactured. In this case, from the viewpoint of anti-reflection, a third phase difference member including a 3rd λ / 4 member can be configured between the optical laminate 100a and the organic EL panel. The third phase difference member can be included in the optical laminate. For example, the optical laminate can have an adhesive layer, a third phase difference member, a polarization member, a first phase difference member, and a protective member in sequence. The third retardation member may be arranged so that the slow axis of the third λ / 4 member forms an angle of, for example, 40° to 50°, 42° to 48°, or about 45° with the absorption axis of the polarization member 10 .
[0124] <Polarization member>
[0125] The polarizing element 10 is typically an absorbing polarizing element including a resin film containing a dichroic substance (sometimes referred to as an absorbing polarizing film), and may further include a protective layer on one or both sides thereof as required. The protective layer is typically bonded to the absorbing polarizing film via any appropriate adhesive layer. As an adhesive forming the adhesive layer, a UV curable adhesive can be typically cited.
[0126] The orthogonal transmittance (Tc) of the polarizing component (absorption type polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and further preferably 0.05% or less. The single transmittance (Ts) of the polarizing component (absorption type polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the polarizing component (absorption type polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.
[0127] The above-mentioned orthogonal transmittance, single transmittance and polarization degree can be measured, for example, using an ultraviolet visible spectrophotometer. The polarization degree P can be measured using an ultraviolet visible spectrophotometer for single transmittance Ts, parallel transmittance Tp and orthogonal transmittance Tc, and the obtained Tp and Tc can be obtained by the following formula. It should be noted that Ts, Tp and Tc are Y values obtained by measuring the 2-degree field of view (C light source) of JIS Z8701 and correcting for visibility.
[0128] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0129] The thickness of the absorption-type polarizing film is, for example, 1 μm to 20 μm, 2 μm to 15 μm, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.
[0130] The absorption-type polarizing film may be produced by a single-layer resin film or by using a laminate of two or more layers.
[0131] In the case of a single-layer resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or a partially saponified ethylene-vinyl acetate copolymer film can be subjected to dyeing treatment using a dichroic substance such as iodine or a dichroic dye, stretching treatment, etc., thereby obtaining an absorption-type polarizing film. Among them, an absorption-type polarizing film obtained by dyeing a PVA film with iodine and uniaxially stretching the film is preferred.
[0132] The dyeing using iodine can be performed by, for example, immersing the PVA film in an iodine aqueous solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching can be performed after the dyeing treatment or while dyeing. In addition, the dyeing can also be performed after the stretching. The PVA film can be subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. as needed.
[0133] As a laminate made using the above-mentioned two or more layers, there can be cited a laminate of a resin substrate and a PVA-type resin layer (PVA-type resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-type resin layer formed by coating on the resin substrate. The absorption-type polarizing film obtained by using a laminate of a resin substrate and a PVA-type resin layer formed by coating on the resin substrate can be made by the following method: for example, a PVA-type resin solution is applied to a resin substrate, dried to form a PVA-type resin layer on the resin substrate, and a laminate of a resin substrate and a PVA-type resin layer is obtained; the laminate is stretched and dyed to make the PVA-type resin layer into an absorption-type polarizing film. In this embodiment, it is preferred to form a polyvinyl alcohol-type resin layer containing a halide and a polyvinyl alcohol-type resin on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. In addition, stretching can further include stretching the laminate in a gas atmosphere at a high temperature (for example, above 95°C) before stretching in a boric acid aqueous solution as needed. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate shrinks by more than 2% in the width direction by heating while being conveyed in the length direction. Representatively, the manufacturing method of the present embodiment includes sequentially performing an auxiliary stretching treatment in a gas atmosphere, a dyeing treatment, a stretching treatment in an aqueous solution, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, the crystallinity of the PVA can be improved even when the PVA is coated on the thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA in advance, it is possible to prevent problems such as the reduction of the orientation and dissolution of the PVA when immersed in water in the subsequent dyeing process and the stretching process, and high optical properties can be achieved. In addition, when the PVA-type resin layer is immersed in a liquid, the orientation disorder of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-type resin layer does not contain a halide. Thus, the optical properties of the absorption-type polarizing film obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and a stretching treatment in an aqueous solution can be improved. Further, the laminate is shrunk in the width direction by drying and shrinking treatment, thereby improving the optical properties. The obtained laminate of resin substrate / absorption type polarizing film can be used directly (that is, the resin substrate can be used as a protective layer of absorption type polarizing film), or the resin substrate can be peeled off from the laminate of resin substrate / absorption type polarizing film, and any appropriate protective layer corresponding to the purpose can be stacked on the peeling surface or on the side opposite to the peeling surface. The details of the manufacturing method of such an absorption type polarizing film are recorded in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The records of these publications as a whole are cited in this specification as a reference.
[0134] The protective layer can be formed by any appropriate film that can be used as a protective layer of the absorption type polarizing film. As a specific example of the material that becomes the main component of the film, there can be cited: cycloolefins (COP) such as polynorbornenes, polyesters such as polyethylene terephthalate (PET), cellulose resins such as triacetyl cellulose (TAC), polycarbonate (PC), (meth) acrylic acid, polyvinyl alcohol, polyamide, polyimide, polyether sulfone, polysulfone, polystyrene, polyolefin, acetate and other transparent resins. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic acid, carbamate, (meth) acrylic acid carbamate, epoxy, silicone, etc. can also be cited. It should be noted that "(meth) acrylic resin" refers to acrylic resin and / or methacrylic resin. In addition, glassy polymers such as siloxane polymers can also be cited. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imido group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl and nitrile group in the side chain can be used, for example, a resin composition having an alternating copolymer formed by isobutylene and N-methylmaleimide and acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above-mentioned resin composition. The material of the resin film can be used alone or in combination.
[0135] The thickness of the protective layer is typically 100 μm or less, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm.
[0136] <1st λ / 4 member>
[0137] The in-plane phase difference Re(550) of the first λ / 4 component 20a is, for example, 100 nm to 190 nm, 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The first λ / 4 component preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases in accordance with the wavelength of the measurement light. The Re(450) / Re(550) of the first λ / 4 component is, for example, not less than 0.75 and less than 1, or not less than 0.8 and not more than 0.95.
[0138] The refractive index characteristics of the first λ / 4 component preferably show a relationship of nx>ny≥nz. Here, "ny=nz" includes not only the case where ny and nz are completely equal, but also the case where they are substantially equal. Therefore, within the range that does not impair the effect of the present invention, ny<nz may sometimes be satisfied. The Nz coefficient of the first λ / 4 component is preferably 0.9 to 3, more preferably 0.9 to 2.5, further preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0139] The first λ / 4 member may be formed of any appropriate material that can satisfy the above-mentioned characteristics. The first λ / 4 member may be, for example, a stretched film of a resin film or an alignment fixing layer of a liquid crystal compound.
[0140] As the resin contained in the above-mentioned resin film, there can be mentioned: polycarbonate resin, polyester carbonate resin, polyester resin, polyvinyl acetal resin, polyarylate resin, cyclic olefin resin, cellulose resin, polyvinyl alcohol resin, polyamide resin, polyimide resin, polyether resin, polystyrene resin, acrylic resin, etc. These resins can be used alone or in combination. As a method of combination, for example, blending and copolymerization can be mentioned. In the case where the first λ / 4 component shows a reverse dispersion wavelength characteristic, a resin film containing a polycarbonate resin or a polyester carbonate resin (hereinafter, sometimes referred to as a polycarbonate resin) can be suitably used.
[0141] As the above-mentioned polycarbonate resin, any appropriate polycarbonate resin can be used. For example, the polycarbonate resin contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from at least one dihydroxy compound selected from alicyclic diols, alicyclic dimethanols, di, tri or polyethylene glycols and alkylene glycols or spirodiols. Preferably, the polycarbonate resin contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, structural units derived from alicyclic dimethanols and / or structural units derived from di, tri or polyethylene glycols; more preferably, it contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from di, tri or polyethylene glycols. The polycarbonate resin may also contain structural units derived from other dihydroxy compounds as needed. It should be noted that details of the polycarbonate resin that can be suitably used for the first λ / 4 component and the method for forming the first λ / 4 component are described in, for example, Japanese Patent Gazette No. 2014-10291, Japanese Patent Gazette No. 2014-26266, Japanese Patent Gazette No. 2015-212816, Japanese Patent Gazette No. 2015-212817, and Japanese Patent Gazette No. 2015-212818, and the records in these gazettes are cited as references in this specification.
[0142] The thickness of the first λ / 4 member formed of a stretched film of a resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, and more preferably 20 μm to 60 μm.
[0143] The orientation fixing layer of the above-mentioned liquid crystal compound is a layer in which the liquid crystal compound is oriented along a given direction within the layer and its orientation state is fixed. It should be noted that the "orientation fixing layer" is a concept that includes an orientation solidification layer obtained by solidifying a liquid crystal monomer as described later. In the 1st λ / 4 component, representatively, the rod-shaped liquid crystal compound is oriented in a state arranged along the slow axis direction of the 1st λ / 4 component (parallel orientation (homogeneous alignment)). As rod-shaped liquid crystal compounds, for example, liquid crystal polymers and liquid crystal monomers can be cited. The liquid crystal compound is preferably capable of polymerization. If the liquid crystal compound is capable of polymerization, the orientation state of the liquid crystal compound can be fixed by polymerizing after orienting the liquid crystal compound.
[0144] The orientation fixing layer (liquid crystal orientation fixing layer) of the above-mentioned liquid crystal compound can be formed by the following method: an orientation treatment is applied to the surface of a given substrate, a coating liquid containing a liquid crystal compound is applied to the surface, and the liquid crystal compound is oriented along the direction corresponding to the above-mentioned orientation treatment to fix the orientation state. As an orientation treatment, any appropriate orientation treatment can be adopted. Specifically, mechanical orientation treatment, physical orientation treatment, and chemical orientation treatment can be cited. As specific examples of mechanical orientation treatment, friction treatment and stretching treatment can be cited. As specific examples of physical orientation treatment, magnetic field orientation treatment and electric field orientation treatment can be cited. As specific examples of chemical orientation treatment, inclined evaporation method and optical orientation treatment can be cited. The processing conditions of various orientation treatments can adopt any appropriate conditions according to the purpose.
[0145] The liquid crystal compound can be aligned by treating it at a temperature corresponding to the type of the liquid crystal compound at which it exhibits a liquid crystal phase. By such a temperature treatment, the liquid crystal compound is in a liquid crystal state and is aligned in the alignment treatment direction of the substrate surface.
[0146] In one embodiment, the alignment state is fixed by cooling the aligned liquid crystal compound as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state can be fixed by subjecting the aligned liquid crystal compound to polymerization or crosslinking treatment as described above.
[0147] As the above-mentioned liquid crystal compound, any appropriate liquid crystal polymer and / or liquid crystal monomer can be used. Liquid crystal polymer and liquid crystal monomer can be used alone or in combination. Specific examples of liquid crystal compounds and methods for making liquid crystal orientation fixing layers are described in, for example, Japanese Patent Publication No. 2006-163343, Japanese Patent Publication No. 2006-178389, and International Publication No. 2018 / 123551. The records of these publications are cited as references in this specification.
[0148] The thickness of the first λ / 4 member composed of the liquid crystal alignment fixing layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and further preferably 1 μm to 4 μm.
[0149] <1st positive C plate>
[0150] The thickness direction phase difference Rth(550) of the first positive C plate 20b is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane phase difference Re(550) of the first positive C plate is, for example, less than 10nm.
[0151] The first positive C plate can be formed of any appropriate material. The first positive C plate is preferably composed of a film containing a liquid crystal material fixed in a homeotropic orientation. The liquid crystal material (liquid crystal compound) capable of homeotropic orientation can be a liquid crystal monomer or a liquid crystal polymer. As a specific example of such a liquid crystal compound and a method for forming a positive C plate, there can be cited the liquid crystal compound and the method for forming the phase difference layer described in
[0020] to
[0028] of Japanese Patent Gazette No. 2002-333642. In this case, the thickness of the first positive C plate is preferably 0.5μm to 5μm.
[0152] <First protection member>
[0153] Typically, the first protective member 41 includes a substrate. The substrate may be composed of any appropriate film. As the material of the main component of the film constituting the substrate, for example, cellulose resins such as triacetyl cellulose (TAC), polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyether sulfones, polysulfones, polystyrenes, cycloolefins such as polynorbornene, polyolefins, (meth) acrylic acid, acetate resins, etc. can be cited. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm.
[0154] The first protective member preferably has a substrate and a surface treatment layer formed on the substrate. The first protective member having a surface treatment layer can be configured so that the surface treatment layer is located on the front side. Specifically, the surface treatment layer can be located on the outermost surface of the optical laminate 100a. The surface treatment layer can have any appropriate function. As the surface treatment layer, for example, a hard coating layer, an anti-reflection layer, an anti-adhesion layer, and an anti-glare layer can be cited. The first protective member can also have more than two layers of surface treatment layers.
[0155] The anti-reflection layer is provided to prevent reflection of external light, etc. As the anti-reflection layer, for example, a fluororesin layer, a resin layer containing nanoparticles (representatively hollow nanoparticles, such as hollow nano silica particles), or an anti-reflection layer having a nanostructure (such as a moth eye structure) can be cited. The thickness of the anti-reflection layer is preferably 0.05 μm to 1 μm. As a method for forming the above-mentioned resin layer, for example, a sol-gel method, a thermal curing method using isocyanate, an ionizing radiation curing method using a cross-linking monomer (such as a multifunctional acrylate) and a photopolymerization initiator (representatively a photocuring method) can be cited. In one embodiment, the anti-reflection layer is provided on the outermost surface of the first protective member, and an inner surface protective film is attached to the surface of the anti-reflection layer. According to the embodiment in which the anti-reflection layer is provided on the outermost surface of the first protective member, an excellent anti-reflection effect can be obtained in a display system in which a space is formed between the semi-reflecting mirror 18 and the first phase difference member 20.
[0156] The hard coat layer preferably has sufficient surface hardness, excellent mechanical strength, and excellent light transmittance. The hard coat layer can be formed of any appropriate resin. Typically, the hard coat layer can be formed of an ultraviolet curable resin. Examples of ultraviolet curable resins include polyesters, acrylics, urethanes, amides, silicones, and epoxies. The thickness of the hard coat layer is, for example, 0.5 μm or more, preferably 1 μm or more, for example, 20 μm or less, preferably 15 μm or less.
[0157] <Adhesive layer>
[0158] The adhesive layer 31 can be composed of any appropriate adhesive. As specific examples, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives can be cited. By adjusting the type, quantity, combination and ratio of the monomers of the base resin forming the adhesive, as well as the amount of the cross-linking agent, the reaction temperature, the reaction time, etc., it is possible to prepare an adhesive with desired characteristics corresponding to the purpose. The base resin of the adhesive can be used alone or in combination of two or more. As the base resin, an acrylic resin can be preferably used. Specifically, the adhesive layer is preferably formed by an acrylic adhesive.
[0159] The thickness of the adhesive layer is typically 1 μm or more, preferably 5 μm or more, more preferably 12 μm or more, and is typically 60 μm or less, preferably 30 μm or less, more preferably 23 μm or less.
[0160] <Release liner>
[0161] The release liner 61 is formed of any appropriate resin film. Specific examples of the material that is the main component of the resin film include polyethylene terephthalate (PET), polyethylene, and polypropylene. The materials of the resin film can be used alone or in combination. The release liner can be transparent (for example, the haze is 5% or less, and for example, 3% or less) or opaque. When inspecting an optical laminate with a surface protective film in a state where the release liner is attached, it is preferred that the release liner is transparent.
[0162] A release treatment layer may be provided on the contact surface of the release liner 61 with the adhesive layer 31. Examples of release treatment agents for forming the release treatment layer include silicone-based release treatment agents, fluorine-based release treatment agents, and long-chain alkyl acrylate-based release treatment agents. The release treatment agents may be used alone or in combination. The thickness of the release treatment layer is typically 50 nm or more and 400 nm or less.
[0163] The thickness of the release liner is typically 5 μm or more, preferably 20 μm or more, and typically 60 μm or less, preferably 45 μm or less. When a release treatment layer is applied, the thickness of the release liner includes the thickness of the release treatment layer.
[0164] Figure 4 Yes, you can Figure 2 A simplified cross-sectional view of another optical laminate used in the exemplified display system. The optical laminate 100b includes an adhesive layer 32, a second phase difference member 22, and a second protective member 42 in sequence. The second phase difference member 22 and the second protective member 42 are stacked together via an adhesive layer 53. The adhesive layer 53 is typically an adhesive layer or an adhesive layer, preferably an adhesive layer. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm. During the period until it is provided for use, the surface of the adhesive layer 32 is protected by a release liner 62. The inner surface protective film and the outer surface protective film are attached to the side surface of the second protective member 42 of the optical laminate 100b.
[0165] exist Figure 4In the example shown, the second phase difference member 22 includes, in addition to the second λ / 4 member 22a, a member (so-called positive C plate) 22b whose refractive index characteristics can show the relationship of nz>nx=ny. The second phase difference member 22 has a stacked structure of the second λ / 4 member 22a and the second positive C plate 22b. Unlike the example shown in the figure, the second positive C plate 22b may be located closer to the second protective member 42 side than the second λ / 4 member 22a, and the second positive C plate 22b may also be omitted. The second λ / 4 member 22a and the second positive C plate 22b may be stacked, for example, via an adhesive layer not shown.
[0166] The optical laminate 100b can be applied to, for example, Figure 2 The manufacturing of the display system of the embodiment in which the second phase difference member 22 is integrally provided in the first lens unit 16 in the exemplary display system. Specifically, by peeling the release liner 62 from the optical laminate 100b and attaching it to the first lens unit 16 via the adhesive layer 32, the display system in which the second phase difference member 22 is integrally provided in the first lens unit 16 can be manufactured.
[0167] <Second λ / 4 member>
[0168] The in-plane phase difference Re(550) of the second λ / 4 component 22a is, for example, 100 nm to 190 nm, 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The second λ / 4 component preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases in accordance with the wavelength of the measurement light. The Re(450) / Re(550) of the second λ / 4 component is, for example, greater than 0.75 and less than 1, or greater than 0.8 and less than 0.95.
[0169] The refractive index characteristics of the second λ / 4 component preferably show a relationship of nx>ny≥nz. Here, "ny=nz" includes not only the case where ny and nz are completely equal, but also the case where they are substantially equal. Therefore, within the range that does not impair the effect of the present invention, ny<nz may sometimes be satisfied. The Nz coefficient of the second λ / 4 component is preferably 0.9 to 3, more preferably 0.9 to 2.5, further preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0170] The second λ / 4 member may be formed of any appropriate material that can satisfy the above-mentioned characteristics. The second λ / 4 member may be, for example, a stretched film of a resin film or an alignment fixing layer of a liquid crystal compound. The same description as that of the first λ / 4 member may be applied to the second λ / 4 member formed of a stretched film of a resin film or an alignment fixing layer of a liquid crystal compound. The first λ / 4 member and the second λ / 4 member may have the same or different configurations (for example, forming materials, thickness, optical properties, etc.).
[0171] <Second positive C plate>
[0172] The thickness direction phase difference Rth(550) of the second positive C plate 22b is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane phase difference Re(550) of the second positive C plate is, for example, less than 10nm.
[0173] The second positive C plate can be formed of any appropriate material that can satisfy the above characteristics. The same description as the first positive C plate can be applied to the constituent material of the second positive C plate. The first positive C plate and the second positive C plate can have the same composition (for example, forming material, thickness, optical properties, etc.) or different compositions.
[0174] <Second protective member>
[0175] The second protective member 42 typically includes a substrate, preferably a substrate and a surface treatment layer formed on the substrate. In this case, the surface treatment layer can be located on the outermost surface of the optical laminate 100b. Regarding the details of the substrate and the surface treatment layer, the same description as the first protective member can be applied. According to an embodiment in which an anti-reflection layer is provided on the outermost surface of the second protective member 42 as a surface treatment layer, in a display system in which the second phase difference member 22 is integrated with the first lens unit 16, the reflective polarization member 14 is integrated with the second lens unit 24, and a space is formed between them, an excellent anti-reflection effect can be obtained.
[0176] The same description as that of the pressure-sensitive adhesive layer 31 and the release liner 61 used in the optical layered body 100 a can be applied to the pressure-sensitive adhesive layer 32 and the release liner 62 used in the optical layered body 100 b , respectively.
[0177] Figure 5 It can be used for Figure 2Schematic cross-sectional view of another optical laminate of the display system exemplified in . The optical laminate 100c includes an adhesive layer 33, an absorptive polarizing element 11, a reflective polarizing element 14 and a third protective element 43 in sequence. The absorption axis of the absorptive polarizing element 11 and the reflection axis of the reflective polarizing element 14 are arranged in a manner substantially parallel to each other, and the transmission axis of the absorptive polarizing element 11 and the transmission axis of the reflective polarizing element 14 are arranged in a manner substantially parallel to each other. The absorptive polarizing element 11, the reflective polarizing element 14 and the third protective element 43 are stacked together via adhesive layers 54 and 55. The adhesive layers 54 and 55 are representatively adhesive layers or adhesive layers, preferably adhesive layers. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm. During the period until it is provided for use, the surface of the adhesive layer 33 is protected by a release liner 63. The inner surface protective film and the outer surface protective film are attached to the side surface of the third protective element 43 of the optical laminate 100c.
[0178] The optical laminate 100c can be applied to, for example, Figure 2 The display system exemplified in the embodiment of the display system further includes an absorptive polarization member between the reflective polarization member 14 and the second lens unit 24. Specifically, by peeling off the release liner 63 from the optical laminate 100c and attaching it to the second lens unit 24 via the adhesive layer 33, a display system in which the reflective polarization member 14 and the absorptive polarization member 11 are integrally provided in the second lens unit 24 can be manufactured.
[0179] <Reflective polarizing member>
[0180] The reflective polarizing component 14 can allow polarized light (representatively linear polarized light) parallel to its transmission axis to pass through while maintaining its polarization state, and reflect light in other polarization states. The orthogonal transmittance (Tc) of the reflective polarizing component can be, for example, 0.01% to 3%. The single transmittance (Ts) of the reflective polarizing component can be, for example, 43% to 49%, and can be preferably 45 to 47%. The polarization degree (P) of the reflective polarizing component can be, for example, 92% to 99.99%. As a reflective polarizing component, it is typically composed of a film with a multilayer structure (sometimes referred to as a reflective polarizing film). Commercially available products of reflective polarizing films include, for example, the trade names "DBEF" and "APF" manufactured by 3M and the trade name "APCF" manufactured by Nitto Denko Corporation.
[0181] <Third protection member>
[0182] The third protective member 43 typically includes a substrate, preferably a substrate and a surface treatment layer formed on the substrate. In this case, the surface treatment layer can be located on the outermost surface of the optical laminate 100c. Regarding the details of the substrate and the surface treatment layer, the same description as the first protective member can be applied. According to an embodiment in which an anti-reflection layer is provided on the outermost surface of the third protective member 43 as a surface treatment layer, an excellent anti-reflection effect can be obtained by integrating the second phase difference member 22 with the first lens unit 16, integrating the reflective polarization member 14 with the second lens unit 24, and forming a display system with a space between them.
[0183] The same description as that of the polarizing element 10 , the pressure-sensitive adhesive layer 31 , and the release liner 61 used in the optical laminate 100 a can be applied to the absorbing polarizing element 11 , the pressure-sensitive adhesive layer 33 , and the release liner 63 used in the optical laminate 100 c .
[0184] B. Method of manufacturing a display system
[0185] According to another aspect of the present invention, there is provided a method for manufacturing a display system (goggles with a display), the method using the optical laminate with a surface protection film described in item A. The method for manufacturing a display system according to one embodiment of the present invention comprises, in sequence:
[0186] Conducting defect inspection on the optical laminate with a surface protection film described in item A;
[0187] Laminating another member on the side of the optical laminate with a surface protection film opposite to the side where the inner surface protection film and the outer surface protection film are laminated to obtain a secondary laminate with a surface protection film;
[0188] peeling the outer surface protection film from the secondary laminate with the surface protection film;
[0189] performing defect inspection on the secondary laminate with the surface protection film; and
[0190] The inner surface protection film was peeled off from the secondary laminate with the surface protection film to obtain a secondary laminate.
[0191] The obtained secondary laminate is subjected to an assembly process and assembled together with other components to form a display system. Figures 6A to 6E For the use of Figure 3 An example of a method for producing a display system of an optical laminate with a surface protection film of the optical laminate 100a exemplified in FIG. 1 will be described.
[0192] like Fig. 6AAs shown, the optical stack 200 with a surface protection film of the inspection object has an optical stack 100a, and the inner surface protection film 110 and the outer surface protection film 120 are sequentially attached to the side surface of the first protective member 41 of the optical stack 100a toward the outside. As defect inspections performed on optical stacks with surface protection films, defect inspections based on naked eye observation and automatic optical inspections (AOI) using a known automatic defect inspection device can be cited. Defect inspections can be either transmission-type or reflection-type. In one embodiment, the defect inspection is reflection-type. In this case, for example, inspection light is irradiated from a light source to the side surface of the outer surface protection film 120 of the optical stack 200 with a surface protection film, and its reflected light image is obtained by a shooting device C such as a line sensor or a two-dimensional camera, and defect detection is performed based on the obtained image data. In another embodiment, the defect inspection is transmission-type. In this case, for example, inspection light is irradiated from a light source onto the side surface of the release liner 61 of the optical laminate 200 with a surface protection film, and its transmitted light image is obtained by the camera C, and defect detection is performed based on the obtained image data. If necessary, the reflective inspection can also be combined with the transmissive inspection. The inspection is preferably carried out in a clean room. As defects to be detected, scratches, foreign matter, bubbles, dirt, etc. can be cited. The size of the defect can be, for example, 45μm to 500μm. It should be noted that for the outer surface protective film and / or the outer side of the release liner of the optical laminate with a surface protection film of the inspection object, another surface protective film can be provided until it is provided for inspection. By peeling off the other surface protective film immediately before the inspection, it is possible to prevent scratches, foreign matter, dirt, etc. from being attached to the surface of the outer surface protective film and / or the release liner, and as a result, it is possible to prevent them from being mistakenly detected as defects of the optical laminate. As such another surface protection film, a surface protection film having adhesiveness to the outer surface protection film or the release liner that is weaker than the adhesiveness to the adherend of the outer surface protection film or the release liner can be preferably used.
[0193] Next, another member is bonded to the side opposite to the side bonded with the inner surface protection film and the outer surface protection film of the optical laminate with surface protection film judged as a qualified product in the above defect inspection to obtain a secondary laminate with surface protection film. Figure 6B As shown, the release liner 61 is peeled off from the optical laminate 200 with a surface protection film, and is bonded to another component 300 through the exposed adhesive layer 31 to obtain a secondary laminate 400a with a surface protection film. In one embodiment, the other component 300 is an optical component such as an organic EL panel, a liquid crystal unit, etc., and the optical laminate with a surface protection film is bonded to its visible side (front) surface.
[0194] When attached to another member 300, the optical laminate 200 with a surface protection film may have a shape corresponding to the shape of the other member 300. For example, the optical laminate 200 with a surface protection film may be formed into a long strip and processed into a desired shape by cutting, punching, cutting, etc. after the above-mentioned defect inspection. Alternatively, the optical laminate 200 with a surface protection film may be processed into a desired shape and then provided for defect inspection.
[0195] Next, if Figure 6C and 6D As shown, the outer surface protection film 120 is peeled off from the secondary laminate 400a with a surface protection film, and the obtained secondary laminate 400b with a surface protection film is subjected to defect inspection. As the defect inspection performed on the secondary laminate with a surface protection film, the same inspection as the defect inspection performed on the optical laminate 200 with a surface protection film can be exemplified.
[0196] Next, if Fig. 6E As shown, the inner surface protection film 110 is peeled off from the secondary laminated body 400b with a surface protection film judged as a non-defective product in the above-mentioned defect inspection, thereby obtaining a secondary laminated body 400c.
[0197] The secondary stack 400c is provided to an assembly process together with other components (e.g., Figure 4 or Figure 5 The optical stack shown in the figure) is assembled together to form a display system.
[0198] According to the above-mentioned manufacturing method, the optical laminate can be inspected for defects multiple times while the surface is protected, and scratches, dirt, etc. can be prevented from being attached to the surface until immediately before being introduced into the display system. Such an effect is particularly advantageous for a situation where the manufacturing of the optical laminate, the manufacturing of an intermediate product (e.g., a display element) using the optical laminate, and the manufacturing (assembly) of a display system using the intermediate product are respectively carried out in different places. In one embodiment, it can be carried out as follows: For an optical laminate manufactured by a manufacturer of the optical laminate, a defect inspection is carried out in the state of an optical laminate with a surface protective film to which inner and outer surface protective films are attached (e.g., Fig. 6A ); the product judged as a qualified product in the defect inspection is shipped to the manufacturer of the display element as a first semi-finished product; the manufacturer of the display element bonds the optical laminate with the surface protection film to an optical component such as a liquid crystal unit and an organic EL panel to manufacture a display element (a liquid crystal display element, an organic EL display element, etc.) (for example, Figure 6B ); then, the outer surface protective film is peeled off, and the defect inspection of the display element is performed in a state protected by the inner surface protective film (for example, Figure 6Cand D); the display element judged as a qualified product in the defect inspection is shipped to the manufacturer of the display system as a second semi-finished product in a state where the inner surface protection film is protected; the display element in a usable state with the inner surface protection film peeled off is provided by the manufacturer of the display system for assembly with other components (for example, Fig. 6E ). According to the manufacturing method of this embodiment, it is possible to appropriately perform defect inspection of the optical laminate as the first semi-finished product, prevent defects (scars, foreign matter, dirt, etc.) when shipping the first semi-finished product that is judged to be a qualified product in the defect inspection, defect inspection when manufacturing the display element as the second semi-finished product, and prevent defects (scars, foreign matter, dirt, etc.) when shipping the second semi-finished product, and as a result, it is possible to contribute to the efficient manufacturing of the final product.
[0199] The manufacturing method of the display system is not limited to the example shown in the figure. For example, the outer surface protective film may be peeled off before the release liner is peeled off and before being bonded to another component, and the second defect inspection may be performed before bonding to another component. In addition, for example, the inner surface protective film may be peeled off after the optical laminate is arranged at a given position of the display system.
[0200] Example
[0201] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. It should be noted that the thickness is a value measured by the following measurement method.
[0202] <Thickness>
[0203] The thickness was measured using a digital micrometer (manufactured by Anritsu Corporation, product name “KC-351C”).
[0204] <In-plane phase difference or phase difference in thickness direction>
[0205] A square sample with a width of 50 mm and a length of 50 mm was cut out from the width center of the member to be measured so that one side was parallel to the width direction of the member to prepare the sample. The in-plane phase difference and thickness direction phase difference of the sample were measured using "KOBRA-WPR" manufactured by Oji Scientific Instruments Co., Ltd.
[0206] [Manufacturing Example 1A: Preparation of Surface Protection Film A]
[0207] <Acrylic polymer A>
[0208] In a reaction container equipped with a thermometer, a stirrer, a condenser and a nitrogen inlet pipe, 100 parts by mass of 2-ethylhexyl acrylate (2EHA) and 4 parts by mass of hexyl acrylate as monomer components, and 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were added together with 150 parts by mass of ethyl acetate, and nitrogen was introduced while slowly stirring at 23°C to replace the nitrogen. Then, the liquid temperature was maintained at about 65°C for 6 hours of polymerization reaction to prepare a solution of acrylic polymer A (concentration 40% by mass). The weight average molecular weight of acrylic polymer A was 530,000.
[0209] <Adhesive composition A>
[0210] Ethyl acetate was added to the solution of acrylic polymer A to dilute it to a concentration of 20% by mass. To 500 parts by mass of the solution (100 parts by mass of solid content), 5 parts by mass of isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) as a crosslinking agent and 0.3 parts by mass of a surfactant ("Aqualon HS-10" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were added and stirred to prepare an adhesive composition A.
[0211] <Surface protection film A>
[0212] The adhesive composition A was applied to the surface (corona treated surface) of a substrate (PET film, "CE901-38" manufactured by KOLON, thickness 38 μm), and then dried to form an adhesive layer (thickness 10 μm). Next, a release liner (manufactured by Toyobo Co., Ltd., product number TG704) was attached to the surface of the adhesive layer opposite to the substrate.
[0213] [Manufacturing Example 1B: Preparation of Surface Protection Film B]
[0214] <Adhesive composition B>
[0215] Ethyl acetate was added to the solution of acrylic polymer A obtained in Production Example 1A to dilute it to a concentration of 20% by mass. 4 parts by mass of isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) as a crosslinking agent and 0.2 parts by mass of a surfactant ("Aqualon HS-10" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were added to 500 parts by mass of the solution (100 parts by mass of solid content) and stirred to prepare an adhesive composition B.
[0216] <Surface protection film B>
[0217] The adhesive composition B was applied to the surface (corona treated surface) of a substrate (PET film, manufactured by Mitsubishi Chemical Corporation, product number T100C38, thickness 38 μm), and then dried to form an adhesive layer (thickness 20 μm). Next, a release liner (manufactured by Toyobo Co., Ltd., product number TG704) was attached to the surface of the adhesive layer opposite to the substrate.
[0218] [Manufacturing Example 1C: Preparation of Surface Protection Film C]
[0219] <Acrylic polymer C>
[0220] In a reaction container equipped with a thermometer, a stirrer, a condenser and a nitrogen inlet pipe, 96.2 parts by mass of 2-ethylhexyl acrylate (2EHA) as a monomer component and 3.8 parts by mass of hydroxyethyl acrylate (HEA) and 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were added together with 150 parts by mass of ethyl acetate, and nitrogen was introduced while slowly stirring at 23°C to replace the nitrogen. Then, the liquid temperature was maintained at about 65°C for 6 hours of polymerization reaction to prepare a solution of acrylic polymer C (concentration 40% by mass). The weight average molecular weight of acrylic polymer C was 540,000.
[0221] <Adhesive composition C>
[0222] Ethyl acetate was added to the solution of acrylic polymer C to dilute it to a concentration of 20 mass %. To 500 mass parts (100 mass parts of solid content) of this solution, 4 mass parts of isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation) as a crosslinking agent and 3 mass parts (0.03 mass parts of solid content) of dibutyltin dilaurate (1 mass % ethyl acetate solution) as a crosslinking catalyst were added and stirred to prepare an adhesive composition C.
[0223] <Surface protection film C>
[0224] A PET film (Mitsubishi Chemical Corporation "Product No. T100C38", thickness 38 μm) was used as a substrate, and the adhesive composition C was applied to its corona-treated surface, and then dried to form an adhesive layer (thickness 5 μm). Next, a release liner (Toyobo Co., Ltd., product No. TG704) was attached to the surface of the adhesive layer opposite to the substrate. Thus, a surface protective film C was obtained.
[0225] [Manufacturing Example 1D: Preparation of Surface Protection Film D]
[0226] A surface protection film D was obtained in the same manner as in Production Example 1C except that a PET film ("CE905-38" manufactured by KOLON, thickness 38 μm) was used as a substrate and the PSA composition C was applied on one side thereof to form a 15 μm thick PSA layer.
[0227] The following (1) and (2) evaluations were performed on the surface protection films A to D. The results are shown in Table 1 together with the thickness of the substrate and the pressure-sensitive adhesive layer.
[0228] (1) Total light transmittance and haze
[0229] For each surface protective film, the release liner was peeled off from the adhesive layer, and light was irradiated from the substrate side using a haze meter ("HZ-V3" manufactured by Suga Test Instruments Co., Ltd.), and the haze was calculated according to Haze (%) = (Td / Tt) × 100 (Td: diffuse transmittance, Tt: total light transmittance) based on JIS-K-7136. The total light transmittance was measured based on JIS-K-7316.
[0230] (2) Peel force
[0231] The surface protective film was cut into a size of 50 mm in width and 100 mm in length. After the release liner was peeled off from the adhesive layer, it was pressed against the adherend with a pressure of 0.25 MPa and a feed speed of 0.3 m / min. After the sample was left to stand for 30 minutes in an environment with a temperature of 23°C and a relative humidity of 50%, a peeling test was carried out in the same environment at a peeling angle of 180° and a tensile speed of 300 mm / min, and the 180° peeling force was measured. It should be noted that, for surface protective films A to C, surface protective film D was used as the adherend, and the peeling force of surface protective film D relative to the substrate side surface was measured. For surface protective film D, the optical laminate A prepared in Example 1 described later was used as the adherend, and its peeling force relative to the side surface of protective component A was measured. The measurement was carried out with N=10, and its average value was taken as the peeling force.
[0232] [Table 1]
[0233]
[0234] *1: Adhesive is surface protection film D
[0235] *2: Adherend is optical laminate A
[0236] [Manufacturing Example 2: Preparation of Polarizing Film A]
[0237] A 30 μm thick polyvinyl alcohol (PVA) resin film (manufactured by Kuraray Co., Ltd., product name "PE3000") was uniaxially stretched in the length direction to 5.9 times the length using a roller stretching machine, and then swollen, dyed, cross-linked, and cleaned, and finally dried to produce an absorption-type polarizing film with a thickness of 12 μm.
[0238] Specifically, the swelling treatment was carried out while being treated in pure water at 20°C and stretched to 2.2 times. Next, the dyeing treatment was carried out while being treated in a 30°C aqueous solution in which the weight ratio of iodine to potassium iodide was 1:7 after the iodine concentration was adjusted so that the monomer transmittance of the obtained absorption-type polarizing film reached 45.0%, and the film was stretched to 1.4 times. Furthermore, the cross-linking treatment adopted a two-stage cross-linking treatment, and the first stage of the cross-linking treatment was treated while being stretched to 1.2 times in an aqueous solution of boric acid and potassium iodide dissolved at 40°C. The boric acid content of the aqueous solution of the first stage of the cross-linking treatment was 5.0% by weight, and the potassium iodide content was 3.0% by weight. The second stage of the cross-linking treatment was treated while being stretched to 1.6 times in an aqueous solution of boric acid and potassium iodide dissolved at 65°C. The boric acid content of the aqueous solution of the second stage of the cross-linking treatment was 4.3% by weight, and the potassium iodide content was 5.0% by weight. In addition, the cleaning treatment was carried out in a potassium iodide aqueous solution at 20°C. The potassium iodide content of the aqueous solution in the washing treatment was adjusted to 2.6 wt %. Finally, the aqueous solution was dried at 70° C. for 5 minutes to obtain an absorption-type polarizing film.
[0239] As protective layers, a triacetylcellulose (TAC) resin film with HC (TAC thickness: 25 μm, HC thickness: 7 μm) was laminated on one side of the obtained absorption-type polarizing film, and a cycloolefin resin film (thickness: 13 μm) was laminated on the other side. Specifically, the curable adhesive was applied so that the total thickness was about 1 μm, and the film was laminated using a roller press. Then, UV light was irradiated from the TAC film side to cure the adhesive.
[0240] Thus, a polarizing film A having a structure of [TAC film (protective layer) / absorptive polarizing film / COP film (protective layer)] was obtained.
[0241] [Manufacturing Example 3: Preparation of λ / 4 Member A]
[0242] The polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC), and 1.19×10-6 parts by mass of calcium acetate monohydrate as a catalyst were added. -2 Mass parts (6.78×10 -5 mol). After the reactor was replaced with nitrogen under reduced pressure, it was heated by a heat medium and stirring was started when the internal temperature reached 100°C. The internal temperature reached 220°C 40 minutes after the start of the temperature rise, and the pressure was reduced while controlling to maintain the temperature, so that it reached 13.3kPa after 90 minutes after reaching 220°C. The phenol vapor produced as a by-product during the polymerization reaction was introduced into a 100°C reflux condenser, so that a certain amount of monomer components contained in the phenol vapor was returned to the reactor, and the uncondensed phenol vapor was introduced into a 45°C condenser for recovery. After nitrogen was introduced into the first reactor to temporarily restore it to atmospheric pressure, the reaction liquid after oligomerization in the first reactor was transferred to the second reactor. Next, the temperature rise and pressure reduction in the second reactor were started, so that it reached an internal temperature of 240°C and a pressure of 0.2kPa after 50 minutes. Then, the polymerization was carried out until the given stirring power was reached. When the predetermined power was reached, nitrogen gas was introduced into the reactor to restore the pressure, and the produced polyester carbonate resin was extruded into water, and the strands were cut to obtain pellets.
[0243] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a long strip of resin film with a thickness of 135 μm was produced using a film-making device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long strip of resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times. Thus, a stretched film (λ / 4 component A) with a thickness of 47 μm was obtained. The Re(590) of the λ / 4 component A is 143 nm, the Re(450) / Re(550) is 0.86, and the Nz coefficient is 1.12.
[0244] [Manufacturing Example 4: Preparation of Positive C Plate A]
[0245] A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side chain liquid crystal polymer represented by the following chemical formula (1) (the numbers 65 and 35 in the formula represent the molar % of the monomer unit, and for convenience, it is represented as a block polymer: the weight average molecular weight is 5000), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Chiba Specialty Chemicals: trade name IRGACURE 907) in 200 parts by weight of cyclopentanone. Then, the coating liquid was applied to a PET substrate subjected to a vertical alignment treatment using a wire bar coater, and then heated and dried at 80°C for 4 minutes to orient the liquid crystal. The liquid crystal layer was irradiated with ultraviolet rays to cure the liquid crystal layer, thereby forming a positive C plate A with a thickness of 4 μm and an Rth (550) of -100 nm on the substrate.
[0246] [Chemical formula 1]
[0247]
[0248] [Manufacturing Example 5: Preparation of Protective Member A]
[0249] The hard coating layer forming material shown below was applied to an acrylic film (thickness 40 μm) having a lactone ring structure, and the coating layer was dried to form a hard coating layer with a thickness of 0.5 μm. Next, the antireflection layer forming coating liquid shown below was applied to the surface of the hard coating layer, heated at 80°C for 1 minute, and the heated coating layer was irradiated with a high pressure mercury lamp with a cumulative light intensity of 300 mJ / cm 2 The coating layer was cured by ultraviolet light to form an antireflection layer with a thickness of 0.1 μm. Thus, a protective member A having a structure of [acrylic film / hard coat layer / antireflection layer] was obtained.
[0250] (Hard coat layer forming material)
[0251] A material for forming a hard coat layer was prepared by adding 0.5 wt % of a leveling agent to an acrylic resin raw material (manufactured by Dainippon Ink Co., Ltd., trade name: GRANDIC PC1071), and further diluting with ethyl acetate so that the solid content concentration reaches 50 wt %. It should be noted that the leveling agent is a copolymer obtained by copolymerizing dimethylsiloxane:hydroxypropylsiloxane:6-isocyanatehexylisocyanuric acid:aliphatic polyester at a molar ratio of 6.3:1.0:2.2:1.0.
[0252] (Coating liquid for forming antireflection layer)
[0253] 100 parts by weight of a multifunctional acrylate containing pentaerythritol triacrylate as the main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 150 parts by weight of hollow nano-silica particles (manufactured by JGC Catalysts & Chemicals Co., Ltd., trade name "THRULYA 5320", solid content 20% by weight, weight average particle size 75 nm), 50 parts by weight of solid nano-silica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle size 10 nm), 12 parts by weight of an additive containing a fluorine element (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD 907", solid content 100% by weight) were mixed. A mixed solvent of TBA (tert-butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 was added to the mixture as a diluent so that the overall solid content reached 4 weight %, and the mixture was stirred to prepare a coating liquid for forming an antireflection layer.
[0254] [Manufacturing Example 6: Preparation of Adhesive Layer A]
[0255] A monomer mixture containing 80.3 parts of butyl acrylate, 16 parts of phenoxyethyl acrylate, 3 parts of N-vinyl-2-pyrrolidone (NVP), 0.3 parts of acrylic acid, and 0.4 parts of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the above-mentioned monomer mixture (solid content), and nitrogen was introduced while slowly stirring to perform nitrogen replacement. Next, the liquid temperature in the flask was maintained at around 55°C and a polymerization reaction was performed for 8 hours to prepare an acrylic polymer solution. The weight average molecular weight of the acrylic polymer is 1.5 million. With respect to 100 parts of the solid content of the obtained acrylic polymer solution, 0.3 parts of benzoyl peroxide (BPO: Nyper BMT manufactured by NOF Corporation) as a crosslinking agent was added to prepare an acrylic adhesive solution.
[0256] The obtained PSA composition was applied to the release-treated layer of a release liner (Cerapeel, manufactured by Toray Industries, Inc.), and dried at 155° C. for 3 minutes to form a 20 μm-thick PSA layer.
[0257] [Example 1]
[0258] The pressure-sensitive adhesive layer A was bonded to the COP protective layer-side surface of the polarizing film A together with the release liner.
[0259] On the other hand, the positive C plate A was bonded to the λ / 4 member A via an ultraviolet curable adhesive (thickness after curing: 1 μm), and then the substrate was peeled off to obtain a phase difference member.
[0260] The obtained phase difference member was bonded to the TAC film side surface of the polarizing film A via an acrylic adhesive layer (thickness 15 μm). At this time, the phase difference member was bonded in such a manner that the λ / 4 member A side surface of the phase difference member became the polarizing film A side, and the angle formed by the absorption axis of the absorption-type polarizing film and the slow axis of the λ / 4 member A was 45°.
[0261] Next, the protective member A was bonded to the surface of the phase difference member via an acrylic adhesive layer (thickness 12 μm). At this time, the protective member A was bonded in such a way that the acrylic film side surface of the protective member A became the phase difference member side (in other words, in such a way that the antireflection layer became the outermost surface). Thus, an optical laminate A having a structure of [release liner / adhesive layer A / polarizing film A / λ / 4 member A / positive C plate A / protective member A] was obtained.
[0262] Next, the release liner is peeled off from the surface protection film D and attached as an inner surface protection film to the protective member A side surface (anti-reflection layer surface) of the optical laminate A. Next, the release liner is peeled off from the surface protection film A and attached as an outer surface protection film to the substrate side surface of the surface protection film D. Thus, an optical laminate with a surface protection film having a structure of [optical laminate A / surface protection film D / surface protection film A] is obtained.
[0263] [Example 2]
[0264] An optical layered body with a surface protection film having a structure of [optical layered body A / surface protection film D / surface protection film B] was obtained in the same manner as in Example 1 except that the surface protection film B was used as the outer surface protection film.
[0265] [Comparative Example 1]
[0266] An optical layered body with a surface protection film having a structure of [optical layered body A / surface protection film D / surface protection film C] was obtained in the same manner as in Example 1 except that the surface protection film C was used as the outer surface protection film.
[0267] <Bubble Evaluation>
[0268] The optical laminate with surface protection film obtained in the above-mentioned embodiment and comparative example was cut into a size of 371.87 mm × 236.58 mm and used as an evaluation sample. The evaluation sample was placed in an automatic optical inspection device, and a reflective appearance inspection was performed to count the number of bubbles existing between the inner surface protection film and the outer surface film. 2 The number of bubbles generated is shown in Table 2.
[0269] <Peeling stability evaluation>
[0270] At room temperature, the optical laminate with surface protection films obtained in the examples and comparative examples was placed on a test bench with the surface protection film side facing upward, and the outer surface protection film was peeled off at a peeling angle of 180° and a peeling speed of 300 mm / min, and evaluated based on the following criteria. The results are shown in Table 2.
[0271] Good: Only the outer surface protective film was peeled off
[0272] Bad: Both the outer and inner surface protective films peeled off
[0273] [Table 2]
[0274]
[0275] As shown in Table 2, in the optical laminate with a surface protection film of the embodiment, the generation of bubbles between the inner surface protection film and the outer surface protection film is suppressed, thereby preventing the erroneous detection of bubbles as defects when the defect inspection is provided. In addition, the optical laminate with a surface protection film having such a structure can be inspected for defects multiple times in a state where the surface protection film is attached, and the surface of the optical laminate can be appropriately protected until the final assembly. In addition, the peeling stability of the optical laminate with a surface protection film of the embodiment is also excellent.
[0276] The present invention is not limited to the above-described embodiments, and various modifications are possible. For example, the above-described embodiments may be replaced with substantially the same configuration, a configuration that exhibits the same effects, or a configuration that achieves the same purpose.
[0277] Industrial Applicability
[0278] The optical laminate with a protective film according to the embodiment of the present invention can be used, for example, for the production of goggles with a display such as VR goggles.
Claims
1. An optical laminate with a surface protection film, comprising: Optical laminate including at least one optical member used for goggles with a display, and A first surface protective film and a second surface protective film are sequentially attached to one surface of the optical laminate toward the outside. in, The first surface protection film comprises a first substrate and a first adhesive layer laminated on the first substrate. The second surface protection film comprises a second substrate and a second adhesive layer laminated on the second substrate. The thickness of the second adhesive layer is 8 μm or more. The peeling force P1 of the first surface protection film with respect to the optical laminate and the peeling force P2 of the second surface protection film with respect to the first surface protection film satisfy the relationship of P2 / P1≤0.
8.
2. The optical laminate with a surface protection film according to claim 1, wherein The peeling force P2 of the second surface protection film with respect to the first surface protection film is 0.5 N / 50 mm or less.
3. The optical laminate with a surface protection film according to claim 1, wherein The total light transmittance of the first surface protection film and the second surface protection film is 85% or more respectively.
4. The optical laminate with a surface protection film according to claim 1, wherein A ratio (L2 / L1) of a total light transmittance L1 of the first surface protection film to a total light transmittance L2 of the second surface protection film is 0.8 to 1.
2.
5. The optical laminate with a surface protection film according to claim 1, wherein The optical stack: (1) an absorbing polarizing member, a first phase difference member, and a protective member are sequentially provided toward the first surface protective film; or, (2) a second phase difference member and a protective member are provided in sequence toward the first surface protective film; or (3) A reflective polarizing member and a protective member are provided in this order toward the first surface protective film.
6. The optical laminate with a surface protection film according to claim 5, wherein The protective member comprises a surface treatment layer, The first surface protection film is attached to the surface treatment layer.
7. The optical laminate with a surface protection film according to claim 6, wherein The surface treatment layer comprises an anti-reflection layer, The first surface protection film is attached to the anti-reflection layer.
8. The optical laminate with a surface protection film according to claim 1, wherein The optical laminate has a pressure-sensitive adhesive layer on a surface opposite to the side on which the first surface protection film and the second surface protection film are bonded.
9. A method for manufacturing a display system, the method comprising: Conducting defect inspection on the optical laminate with a surface protection film according to any one of claims 1 to 8; Laminating another member on the side of the optical laminate with a surface protection film opposite to the side on which the first surface protection film and the second surface protection film are laminated to obtain a secondary laminate with a surface protection film; peeling the second surface protection film from the secondary laminate with the surface protection film; Conducting defect inspection on the secondary laminate with the surface protection film; as well as The first surface protection film is peeled off from the secondary laminate with the surface protection film to obtain a secondary laminate, Among them, the display system is goggles with a display.
Citation Information
Patent Citations
Optically active liquid crystal compound having cyano group
JP1989070455A
Protective film for polarizer and its manufacturing method
JP2001343529A
Homeotropic alignment liquid-crystalline composition, method for producing homeotropic alignment liquid crystal film and homeotropic alignment liquid crystal film
JP2002333642A
Elliptical polarization plate and picture display device using it
JP2006163343A
Method of producing elliptically polarizing plate and image display using the elliptically polarizing plate
JP2006178389A